Liver functions and medication adherence in tuberculosis patients after 6 months of antituberculosis treatment in Indonesia - Dyah Aryani Perwitasari; Triantoro Safaria; Didik Setiawan; Haafizah Dania; Salma Auliya Fatimah; Imaniar Noor Faridah (Journal of International Medical Research)
Objective The objective of this study was to assess liver functions in tuberculosis patients after 6 months of treatment and determine the difference in the level of liver enzymes based on medication adherence and patient characteristics. Methods We used a prospective cohort design. The inclusion criteria were adult tuberculosis patients treated with the first line of antituberculosis drugs. The patients’ adherence to medication was measured using the Medication Adherence Rate Scale questionnaire. We also measured the total bilirubin, aspartate aminotransferase, and alanine aminotransferase levels over 2, 4, and 6 months of treatment. Results There were 233 tuberculosis patients enrolled in this study, with 58.91% male patients and the mean age of 40.31 (SD: 18.00) years. Overall, 86.3% of the patients had good medication adherence. The patients reported increased levels of aspartate aminotransferase (40%) and alanine aminotransferase (64%). There were no significant differences in total bilirubin between the adherence groups. Tuberculosis patients with poor adherence showed significantly increased levels of alanine aminotransferase and aspartate aminotransferase levels (p < 0.05). Female patients with poor adherence had high levels of alanine aminotransferase and aspartate aminotransferase. Conclusion The monitoring of alanine aminotransferase and aspartate aminotransferase in tuberculosis patients should be implemented during the 2nd, 4th, and 6th months of treatment, especially in female patients.